Biases for Evil and Moral Perfection - Eyghen, Hans van ca. 21. Jh. (Religions, 2021)
I argue that deeply ingrained dispositions to do evil do not render moral perfection impossible. I discuss various accounts of moral perfection and the evidence from cognitive (neuro)science that points towards a strong disposition for evil. Afterwards, I discuss three strategies that can allow humans to overcome their evil dispositions. These are: cognitive enhancement, avoiding triggering situations and structural solutions.